From Hard Currency Policy to Monetary Union - Heinz Handler (Austrian Institute of Economic Research (WIFO), 2003)
In the wake of monetary integration in Europe, Austria abandoned the tested hard currency policy (HCP) for joining EMU as a member. The final target of monetary policy and real sector adjustment needs are similar in both regimes, and the HCP may therefore be viewed as a convenient "training camp" for later EMU accession. Georg Winckler devoted a number of essays on the critique, but also on the analytical foundation, of the HCP. The current paper takes up some of the strands developed by him, and reviews the implications on Austria's monetary strategy of the changeover to EMU. At EMU level it was required to newly establish credibility and accountability of the monetary authorities. Towards this end, the ECB emitted harsh signals to be committed to its primary task of maintaining price stability, and it was therefore held accountable for neglecting real sector developments as well as potential threats of deflation. This is unjustified, given the circumstances the ECB has been faced with since its inception, including the marked swings in the dollar value of the euro. The ECB could be blamed, however, for the lack of transparency with regard to its monetary strategy (which it declines to be "inflation targeting"): it resorts to a rather vaguely defined final monetary target, it does not observe an intermediate target, and it is by no means clear what purpose the reference value for money growth does serve. The paper concludes that in Europe there is no immediate danger that the goal of price stability could unintentionally end up in deflation.
Keywords: 330; Wechselkurspolitik; Wechselkurssystem; Eurozone; Österreich